BỘ VI ĐIỀU KHIỂN ĐA NĂNG - Hùng, Trần Thanh; Danh, Trần Hữu (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract This research develops a multipurpose microcontroller system (MPC) to help technicians and students in study and design control systems. Based on an 8951 microcontroller, the MPC is built to satisfy almost basic needs of control. Using the MPC, technicians and students can develop control applications easily and quickly. Based on an efficient algorithm, the MPC has ability to run program by steps or by blocks, thing that can not be done by 8951. This is very important in designing control systems because users can stop application programs at any points to look for errors not only in software but also in hardware. With such abilities, MPC is very helpful for everyone in studying microcontroller technique and designing control systems. Keyword: MPC- multipurpose microcontroller, step, block, AutoRun, ISR. Title: Multipurpose Microcontroller